Education Using ICT for Construction Management - Alfredo Soeiro (2008)
A project carried through between institutions of higher education and construction companies was co-financed by the European Commission. The project lasted three years where the main objective was to develop the staff training in using and applying the Information and Communication Technologies (ICT) in construction management. The results of the project have been also used in a new course of the senior year in specialization area of construction of the Civil Engineering degree of the University of Porto. Some conclusions of the diverse experiences of the project partners are also presented indicating future developments in this area.